CPW-fed elliptical shaped patch antenna with RF switches for wireless applications. (May 2021) - Sailaja, B.V.S.; Naik, Ketavath Kumar
Abstract: In this work a novel reconfigurable antenna with RF-MEMS switch is presented for wireless applications. The analysis has been carried out for RF-MEMS switch, antenna device, and integration of antenna with switch. The CPW-fed elliptical shaped patch antenna with split ring resonator (SRR) is embedded on the patch and it resonates at 8.09 ​GHz. The analysis of RF-MEMS switch is carried out for its performance parameters. The RF-MEMS switch is integrated on to the elliptical patch antenna resonates at X-band used for wireless applications. The frequency shift is observed at 8.2 ​GHz for ON state and 8.5 ​GHz for OFF state of RF-MEMS switch conditions on elliptical patch antenna. The proposed device analysis is also carried out with theoretical and simulated results. The novelty of the proposed elliptical shaped reconfigurable patch antenna is incorporated with RF MEMS switch achieves compact dimension of 33 ​× ​40 ​× ​1.6 ​mm 3, the radiation gain is of greater than 7 ​dB, the impedance bandwidth of 400 ​MHz and 90% radiation efficiency.